A case of Cornelia de Lange syndrome from Sudan - Elagib Atif; Nilsson Therese; Gisselsson David; Ellaithi Mona; Fadl-Elmula Imad; Abdelgadir Mashair (BMC, 2007)
Abstract Background Brachmann de Lange syndrome (BDLS) is a multiple congenital anomaly syndrome characterized by a distinctive facial appearance, prenatal and postnatal growth deficiency, psychomotor delay, behavioral problems, and malformations of the upper extremities. Case presentation Here we present for the first time a case of BDLS from Sudan, a 7-month-old female infant, who was referred as a case of malnutrition. The patient was from a Sudanese western tribe. Clinical investigation showed that the child was a classical case of BDLS, but with some additional clinical findings not previously reported including crowded ribs and tied tongue. Conclusion Reporting BDLS cases of different ethnic backgrounds could add nuances to the phenotypic description of the syndrome and be helpful in diagnosis.